Functionalized Cyclopropenes and Methylenecyclopropenes from Dianions of 3-Hydroxymethylcyclopropenes - Hassink, Matthew D.; Fox, Joseph M. (Synthesis, 2012)
1,2-Disubstituted 3-hydroxymethylcyclopropene derivatives have been synthesized by reacting the dianions of 1-alkyl-3-hydroxymethylcyclopropenes with a range of electrophiles. Additionally, a complementary procedure is described for one-pot sequential alkylation/rearrangement to provide a convenient synthesis of a chiral methylenecyclopropane directly from a 1-alkyl-3-hydroxymethylcyclopropene.
Keywords: cyclopropene; chirality; dianions; strained ring systems; rearrangement